Asian collection 50 : from the collection of the Fukuoka Asian Art Museum. - Masahiro, Ushiroshoji; Raiji, Kuroda; Tomomichi, Nakao; Toshiko, Rawanchaikul; Yuko, Yamaki; Fukuoka Asian Art Museum, Fukuoka (Fukuoka : Fukuoka Asian Art Museum, 2000)
Alesworth, David ; Arellano, Agnes ; Bendi, Wayan ; Borlongan, Elmer ; Cai Guo-Qiang ; Christanto, Dadang ; Chusin Setiadikara ; Dadi, Elizabeth ; Dadi, Iftikhar ; Das, R.K. ; Devi, Bauwa ; Dono, Heri ; Duchanee, Thawan ; Duck-Hyun, Cho ; Emjaroen, Pratuang ; Fang Lijun ; Feleo, Roberto ; Francisco, Carlos V. ; Haider Raza, Syed ; Hendra Gunawan ; Heng, Amanda ; I Dewa Putu Mokoh ; Ijaz-ul-Hassan, Mian ; Kang, Liu ; Kazi, Durriya ; Lu Shengzhong ; Luo Brothers ; Mistry, Dhruva ; Nair, Surendran ; Nguyen Phan Chanh ; Ocampo, Manuel ; Reddy, Ravinder ; Roy, Jamini ; Sidharta, Gregorius ; Tan Chinkuan ; Tang Dawu ; Tsagaandariin Enkhjargal ; Tschang-yeul Kim ; Tserennadmidin Tsegmed ; Tsuyoshi, Ozawa ; Wang Hongjian ; Whanki, Kim ; Wu Tien-chang ; Xu Bing ; Yun Soknam ; Zhang Peili
Engels
Japans
Asian collection 50 : from the collection of the Fukuoka Asian Art Museum, FAAM (Fukuoka Asian Art Museum) Fukuoka, 2000
boek